2013
DOI: 10.1016/j.rmed.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Severity of pulmonary involvement and 18F-FDG PET activity in sarcoidosis

Abstract: The severity of the pulmonary involvement, assessed by HRCT features and lung function parameters, appeared to be associated with PET activity in sarcoidosis. The majority of patients with fibrotic changes demonstrated inflammatory activity at pulmonary and extrathoracic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 35 publications
0
59
0
2
Order By: Relevance
“…There is also increasing interest in fluorodeoxyglucose-PET/computed tomography (FDG-PET CT) scans to detect metabolic activity in granulomas. Mostard et al retrospectively assessed 95 patients with sarcoidosis for whole body PET scan and HRCT findings (38). Overall, pulmonary PET positivity was detected in 56 patients (59%), and the vast majority of patients with fibrotic changes on HRCT had positive PET findings.…”
Section: Part Iii: Clinical Management Of Fibrotic Sarcoidosismentioning
confidence: 99%
“…There is also increasing interest in fluorodeoxyglucose-PET/computed tomography (FDG-PET CT) scans to detect metabolic activity in granulomas. Mostard et al retrospectively assessed 95 patients with sarcoidosis for whole body PET scan and HRCT findings (38). Overall, pulmonary PET positivity was detected in 56 patients (59%), and the vast majority of patients with fibrotic changes on HRCT had positive PET findings.…”
Section: Part Iii: Clinical Management Of Fibrotic Sarcoidosismentioning
confidence: 99%
“…Whether or not masses are fibrotic cannot always be differentiated on HRCT. Only serial imaging or PET/CT can demonstrate if they are fibrotic or also represent active inflammatory disease [22]. These hilar masses were regarded as consolidations and scored as being central or peripheral in location.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirm these findings. [45] In addition, one study, reported 100% sensitivity of PET-CT for pulmonary and systemic sarcoidosis compared with 81% sensitivity for 67Ga scintigraphy/single photon emission computed tomography (SPECT) and showed positive PET-CT results in cases with negative 67Ga scans. [1] Thus, in our study 67Ga scan was not done.…”
Section: Discussionmentioning
confidence: 99%